PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD BERBANTUAN MEDIA RODA PINTAR BERKANTONG TERHADAP HASIL BELAJAR MATEMATIKA - Silviana Nur Faizah; Lia Nur Atiqoh Bela Dina; Eddy Sutadji; Erika Nur Hayati; Aynin Mashfufah (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2023)
Mathematical learning innovation demands teachers to equip students with mathematical literacy in the industrial era 4.0. This study aimed to determine the effect of the STAD-type cooperative learning model assisted by Roda Pintar Berkantong media on mathematics learning outcomes. The implementation of the quantitative method of the One Group Pretest-Posttest design in this study was supported by observation instruments, interviews, tests (pretest and posttest), and documentation (RPP). Then the data were analyzed using the scoring technique, mean, N-Gain, to test the research hypothesis and the normality test was carried out, followed by the Wilcoxon test. The results showed that the learning outcomes of the posttest (77.75) > the learning outcomes of the pretest (62.5) with an increase in learning outcomes (N-Gain) in the moderate category (0.49). Wilcoxon test results showed Asymp. Sig. 2-tailed (0.000) < 0.05 indicates that the STAD-type cooperative learning model assisted by Roda Pintar Berkantong media significantly affects the mathematics learning results on geometric material